2016
DOI: 10.17236/sat00089
|View full text |Cite
|
Sign up to set email alerts
|

Uroliths of cats in Switzerland from 2002 to 2009

Abstract: In this study data on composition of uroliths collected from cats and epidemiologic data of affected cats in Switzerland from 2002 to 2009 are summarised. Of 884 stones analysed 50% (n=441) were composed of calcium oxalate, 45% (n=398) of struvite, 3% (n=18) of ammonium urate, 1% (n=12) were mixed stones, 1% (n=9) were composed of silica, 3 stones were solidified blood, 2 consisted of cystine and 1of xanthine. 40% of the ureteral stones were composed of struvite. Domestic cats had significantly less calcium ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 8 publications
3
17
0
3
Order By: Relevance
“…In this study, there was a significant risk for cats in the age groups of 1–6 years and 7–10 years, with an average age of 6.5 ± 3.6 years, similar to other studies. 1,3 Regarding the frequency of cases in different breeds, DSH cats were the most commonly affected; however, no significant differences were found when compared with the control group ( P = 0.47). Houston et al 4 found that Persian and Siamese cats are predisposed to forming CaOx uroliths vs domestic shorthair cats, and noted that domestic longhair cats were more likely to form struvite stones.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this study, there was a significant risk for cats in the age groups of 1–6 years and 7–10 years, with an average age of 6.5 ± 3.6 years, similar to other studies. 1,3 Regarding the frequency of cases in different breeds, DSH cats were the most commonly affected; however, no significant differences were found when compared with the control group ( P = 0.47). Houston et al 4 found that Persian and Siamese cats are predisposed to forming CaOx uroliths vs domestic shorthair cats, and noted that domestic longhair cats were more likely to form struvite stones.…”
Section: Discussionmentioning
confidence: 80%
“…Other studies have observed a higher frequency of urolithiasis in males. 1,3,4 Predisposed cats can form uroliths at any age. In this study, there was a significant risk for cats in the age groups of 1–6 years and 7–10 years, with an average age of 6.5 ± 3.6 years, similar to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…This fact can be confirmed by increasing number of owners of pets with urolithiasis, looking for help in veterinary clinics (3,4). Urolithiasis is widespread disease, could be found in many species, including cats, dogs, rabbits, guinea-pigs, turtles etc (1,(4)(5)(6). Despite the large scale of this pathology in animal world, there are some challenges with diagnostic process and diagnosis's verification (1,7).…”
Section: Introductionmentioning
confidence: 95%
“…In 1991, a cystinuric domestic cat was first described (4) and in 1999 eighteen cases were briefly summarized (34). According to urolith laboratories, cystine calculi represent only up to 0.5% in Germany (and neighboring countries) (7, 13) and 0.1% of all feline uroliths in North America (31) compared with 4.4% of all canine calculi in Europe (12) and 0.3–1% in North America (31). Cystinuria was reported equally in male and female cats and independently of neuter status and thus an androgen-dependent cystinuria type seems unlikely (34).…”
Section: Introductionmentioning
confidence: 99%